A dozen lessons for entrepreneurs - Griffin, Trenholme J. (Tantor Audio, 2018)
From profiles and interviews with the world's leading venture capitalists and high-profile coaches of business founders, A Dozen Lessons distills a set of bedrock methods for approaching business questions and creating value.